Using Short Stories in EFL Classroom - Eliza, Tiara (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2020)
English is taught as a foreign language in Indonesia in which students are exposed to English only during the classroom. Students who do not use English in their everyday livewould experience them less knowledge of English. This becomes a challenge for the teachers to make a difference. As English is the target language in which students must be proficient in this global era, it makes even the more difficult. Consequently, to overcome these challenges, teachers need to find an effective way or strategy to use in teaching and learning process. Teachers should make the students keep concentrating and make the situation as interesting as possible in order to attract them to learn. Short story is considered as one of the literary genres that can be used as the material to make English learning more interesting. This paper aims to present how short story can be used in EFL classroom.